1998
DOI: 10.1021/jm980317y
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Models for GABAA/Benzodiazepine Receptor Subtypes:  Studies of Quantitative Structure−Activity Relationships for Imidazobenzodiazepines at Five Recombinant GABAA/Benzodiazepine Receptor Subtypes [αxβ3γ2 (x = 1−3, 5, and 6)] via Comparative Molecular Field Analysis

Abstract: Affinities of a series of substituted imidazobenzodiazepines at recombinant alpha1beta3gamma2, alpha2beta3gamma2, alpha3beta3gamma2, alpha5beta3gamma2, and alpha6beta3gamma2 GABAA/benzodiazepine receptor subtypes are reported. Many of these ligands displayed high affinities (low-nanomolar to subnanomolar scale) at all five receptor subtypes. Furthermore, a number of imidazobenzodiazepines exhibited relatively good selectivity at the alpha5-containing receptor isoform. For example, ligand 27 (RY-023) demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 35 publications
3
56
0
Order By: Relevance
“…This compound has been described as a positive allosteric modulator with a K i value of 34 nM (41). A model based on quantitative structure/activity relationships developed by Huang et al (11) proposed only a partial superposition of diazepam with the imidazobenzodiazepine RY-80, which carries an acetylenic group instead of the azide group of Ro15-4513, to satisfy a putative common hydrogen donor site. However, the same condition can also be met if the alignment is assumed to be precise, and the protein is allowed to change conformation.…”
Section: Irreversible Reaction Of the Imid-ncs Compound Withmentioning
confidence: 99%
“…This compound has been described as a positive allosteric modulator with a K i value of 34 nM (41). A model based on quantitative structure/activity relationships developed by Huang et al (11) proposed only a partial superposition of diazepam with the imidazobenzodiazepine RY-80, which carries an acetylenic group instead of the azide group of Ro15-4513, to satisfy a putative common hydrogen donor site. However, the same condition can also be met if the alignment is assumed to be precise, and the protein is allowed to change conformation.…”
Section: Irreversible Reaction Of the Imid-ncs Compound Withmentioning
confidence: 99%
“…Previous attempts have been made to superimpose the structures of allosteric modulators to construct a pharmacophore model for the BZD recognition site (Borea et al, 1987;Villar et al, 1989;Schove et al, 1994;Zhang et al, 1995;Huang et al, 1998Huang et al, , 1999He et al, 2000;Marder et al, 2001;Verli et al, 2002). However, such models are difficult to relate to receptor structure.…”
mentioning
confidence: 99%
“…Cook also carried out CoMFA-based 3D QSAR studies on a series of substituted imidazobenzodiazepines using affinity values reported for the recombinant a 1 b 3 g 2 , a 2 b 3 g 2 , a 3 b 3 g 2 , a 5 b 3 g 2 , and a 6 b 3 g 2 GABA A /BZ receptor subtypes to deduce predictive pharmacophore models [85]. Inspection of these models suggested that L 2 site within the pharmacophore/receptor model of the a 1 b 3 g 2 receptor subtype corresponds to the region occupied by a C-8 substituent in [11] CL-218,872 (K i = 57 nM at α1) [11] the unified pharmacophore/receptor model.…”
Section: A Predictive Pharmacophore Model For Flavonoidsmentioning
confidence: 99%